Developing a Workplace-Based Learning Culture in the NHS: Aspirations and Challenges. (July 2020) - Gawne, Suzanne; Fish, Rebecca; Machin, Laura
Background: The delivery of patient care in the United Kingdom is under increasing financial pressure. The need to continuously improve service delivery while making financial savings is challenging. Alongside this, National Health Service (NHS) Trusts must provide a suitable educational environment that meets the needs of all learners while meeting performance standards and targets set by external regulating authorities. This research addresses the gap in literature concerning educational culture in the NHS. Methods: This case study examines the delivery of postgraduate medical education in the workplace. Semi-structured interviews were conducted with 6 lead educators in the Medical Division of a North West NHS Trust to glean their insights into what works and what needs to change. Results: A thematic analysis of the transcripts revealed a number of factors that facilitated and hindered educational opportunities for doctors in training, including the role of leadership, the demands of external regulatory authorities, and the pressures on frontline staff to deliver safe, personal, and effective care. Conclusion: Opportunities for developing a collaborative approach between educational and clinical leaders and the individuals delivering education in the workplace to enhance the educational environment are discussed. Finally, an evaluatory toolkit based on the themes emerging from the data is proposed, as a resource for other health care organisations to help improve the delivery of workplace-based medical education.